A Comprehensive Study of the Trends and Analysis of Distributed Ledger Technology and Blockchain Technology in the Healthcare Industry - Thakur, Anusha (Frontiers in Blockchain, 2022)
In today’s scenario, it is essential for the healthcare sector to focus on balancing patient care records with information relevant to completeness, accessibility, and privacy concerns. Advancements in information technology and health infrastructure exponentially bolster transformative changes in the healthcare industry. Incorporation of blockchain along with distributed ledger technology (DLT) owes the potentiality to cater to the interoperability restraints in health IT systems and enables medical researchers, healthcare entities, and healthcare providers to share electronic health data in a secured and well-mannered system. In addition to these, such technologies also propose and offer latest models for health statistics exchange by making the records more secure and efficient. However, successful implementation of blockchain technology and DLT necessitates efficient infrastructure, connectivity, and other factors. Hence, there poses to be several challenges restraining the mainstream usage of blockchain technology in the healthcare sector. The article illustrates different generations of blockchain, issues in healthcare data, and network structures as well as the solutions offered by the sector to cater to such problems. In addition to these, the article also emphasizes on the different application areas of blockchain and DLT in healthcare infrastructure. This article further discusses latest trends and factors driving the need for the incorporation of blockchain and distributed ledger technology in the healthcare sector and the future scenario for the same.